Arrhythmias in Patients with Congenital Heart Disease: a Modern View of the Problem - O. S. Stychynskyi; P. O. Almiz; A. V. Topchii; M. M. Petkanych; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2019)
Thanks to the successes of modern cardiac surgery, more and more patients with congenital heart disease (CHD) reach adulthood, with approximately one in four having various heart rhythm disturbances. Their causes are both the CHD themselves and the consequences of surgical or interventional intervention. Arrhythmias in this category of patients worsen the quality of life, lead to serious complications, and can cause sudden cardiac death. The paper summarizes and analyzes current trends and recommendations of the world’s leading specialized communities for the management of patients with congenital heart disease with cardiac arrhythmias.The article reflects approaches to the management and monitoring of this category of patients, including asymptomatic ones. The necessity of early detection of arrhythmia and the involvement of a team of specialists in specialized centers for the development of tactics and treatment after surgical correction is justified. Also discussed are the issues of indications for electrophysiological research and its feasibility, the possibility and effectiveness of catheter destruction, the need for continuous drug therapy, indications for implantation of artificial pacemakers and cardioverter-defibrillators. The paper also reflects the question of various mechanisms of the development of arrhythmia in patients after surgical correction of congenital heart defects, as well as highlighted the possible ways of preventing arrhythmogenesis in patients after surgical correction.